Masking of vertebral artery dissection by severe trauma to the cervical spine - Schellinger, Peter; Schwab, Stefan; Krieger, Derk; Fiebach, Jochen B.; Steiner, Thorsten; Hund, Ernst; Hacke, Werner; Meinck, Hans-Michael (Spine, 2001)
Study Design: A prospective case study was performed. - Objectives: To illustrate the association of cervical trauma with vertebral artery dissection, and to propose a diagnostic and therapeutic algorithm for suspected traumatic vertebral artery dissection. - Summary of Background Data: Vertebral artery dissection is a recognized but underdiagnosed complication of trauma to the cervical spine. Symptoms of spinal cord injury, however, may obscure those of vertebral artery dissection, presumably causing gross underdiagnosis of this complication. - Methods: All patients with vertebral artery dissection admitted to the authors’ facility between 1992 and 1997 were screened for cervical trauma. - Results: This article presents four patients with severe trauma to the cervical spine, defined as luxation, subluxation, or fracture, in whom symptoms of vertebral artery dissection developed after a delay ranging from several hours to weeks. The traumatic vertebral artery dissection typically was located at the site of vertebral injury or cranial to it. One patient with fracture of the odontoid process survived symptom free without ischemic brain infarctions. Another patient survived with traumatic quadriplegia in addition to large cerebellar and posterior cerebral artery infarctions. Two patients died as a result of fulminant vertebrobasilar infarctions, both with only moderate impairment from the primary spinal cord injury. - Conclusions: Early signs of vertebral artery dissection include head and neck pain, often localized to the site of intimal disruption, which may be disguised by the signs of the spinal injury. Early Doppler ultrasound and duplex sonography as a noninvasive screening method should be performed for patients with severe trauma to the cervical spine. In cases of vertebral artery dissection, immediate anticoagulation should be initiated. Traumatologists should be aware of this complication in evaluating patients with severe trauma of the cervical spine, and also for a variety of forensic reasons.